CELLCOUNTER: Novel Open-Source Software for Counting Cell Migration and Invasion In Vitro. (26th June 2014) - Li, Xiaoni; Yang, Hongshun; Huang, Hailiang; Zhu, Tao
Abstract : Transwell Boyden chamber based migration/invasion assay is a simple and extensively used approach for the characterization of cell motility in vitro . Cell motility is quantified by counting the number of cells that pass through the filter membrane. The counting is usually performed manually, which is laborious and error prone. We have therefore developed CELLCOUNTER, an application that is capable of recognizing and counting the total number of cells through an intuitive graphical user interface. The counting can be performed in batch, and the counting results can be visualized and further curated manually. CELLCOUNTER will be helpful in streamlining the experimental process and improving the reliability of the data acquisition.